2020
DOI: 10.1109/access.2020.2971253
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Prediction Scheme of Water Quality in Smart Mariculture With Deep Bi-S-SRU Learning Network

Abstract: In the smart mariculture, the timely and accurate predictions of water quality can help farmers take countermeasures before the ecological environment deteriorates seriously. However, the openness of the mariculture environment makes the variation of water quality nonlinear, dynamic and complex. Traditional methods face challenges in prediction accuracy and generalization performance. To address these problems, an accurate water quality prediction scheme is proposed for pH, water temperature and dissolved oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Jaloree et al [ 17 ] have attempted to predict the WQ of the Narmada River with five WQ indicators using a decision tree model. Another study suggested the use of the deep Bidirectional Stacked Simple Recurrent Unit (Bi-S-SRU) [ 18 ] for the designing of a precise forecasting scheme of the WQ in smart mariculture.…”
Section: Introductionmentioning
confidence: 99%
“…Jaloree et al [ 17 ] have attempted to predict the WQ of the Narmada River with five WQ indicators using a decision tree model. Another study suggested the use of the deep Bidirectional Stacked Simple Recurrent Unit (Bi-S-SRU) [ 18 ] for the designing of a precise forecasting scheme of the WQ in smart mariculture.…”
Section: Introductionmentioning
confidence: 99%
“…Several models based on different prediction methods have been developed for DO concentration forecasting in aquaculture ecosystems [11][12][13][14][15][16][17]. Xiao et al [11] applied back propagation (BP) NN method with the combination of purelin, logsig, and tansig activation functions to propose a prediction model for DO concentration in aquaculture.…”
Section: Related Literature Reviewmentioning
confidence: 99%
“…The effect of their proposed model in practical application shows that the designed system can use both neural network and decision tree methods to forecast DO concentration and conduct early warning by value forecasting and rule-based reasoning, respectively. Liu et al [15] proposed a prediction model for water quality in smart mariculture with deep Bi-directional Stacked Simple Recurrent Unit (Bi-S-SRU) learning network. Yan et al [16] applied deep belief network and least squares support vector regression (LSSVR) machine to propose a forecasting model based on cross-section water quality.…”
Section: Related Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, GRU has achieved good application results in fields of time series data prediction such as meteorology [17], wind power [18], and pond aquaculture water [19]. To efficiently integrate relevant information in the context of time series data, Liu Juntao [20] and other scholars have successfully applied the bidirectional stacked simple recursive unit (Bi-S-SRU) to water quality prediction of marine aquaculture, demonstrating the feasibility of bidirectional neural network to predict water quality parameters. Aiming at the problem of PM2.5 air pollution prediction, Qing et al [21] adopted a new hybrid algorithm of one-dimensional convolution neural network (1-DCNN) and bi-directional gated recurrent units (BiGRU), which fully excavated the local characteristics of meteorological data from different sources.…”
Section: Introductionmentioning
confidence: 99%